HARİZMİ’NİN MEFATİHU’L-ULUM’UNDA MANTIK - İbrahim Çapak (İslami İlimler Dergisi)
Al-Khawârizmî lived in the tenth century as a bureaucrat. He only has a book called Mafatih al-ulum. He has written this book for managers in the his period. Analyzes several sciences in this book. One of the issues he addresses is the logic. Al-Kharizmi examines Isagoge, Categries, Perihermenias, Analititics, Apodiktics, Topics, Sophistics Rhetoric, Poetics. In this study we will study Al-Khawârizmî’s views about logic.